Relationships between upper trunk rotation kinematics and arm fatigue after repetitive pitching among baseball pitchers - Mine, K.; Jones, M.; Saunders, S.; Onofrio, B.; Crowther, R. G.; Milanese, S. (Sports Biomechanics, 2025)
Early upper trunk rotation during baseball pitching has been associated with higher upper-limb kinetics. However, its relationship with arm fatigue after repetitive pitching is unclear. This study aimed to investigate associations between upper trunk rotation kinematics and arm fatigue. A total of 14 healthy male pitchers (age 27.1 ± . 9.0 yrs) threw 45 pitches across three innings. Pitching mechanics and ball velocity were assessed using 3-D motion analysis (Vicon, UK) and Rapsodo (Rapsodo, USA). Subjective arm fatigue was assessed by CR-10 Borg scale, whereas grip and shoulder external rotation strength were evaluated before and after pitching sessions. Ball velocity and the timing of upper trunk rotation did not change significantly throughout the three innings. Three-inning pitching produced significant levels of subjective and objective arm fatigue. The onset timing of upper trunk rotation (OTUTR) had significant effects on CR-10 Borg scale and ball velocity. The magnitude of effect of OTUTR on ball velocity may be clinically significant. These findings suggest that the timing of upper trunk rotation may not significantly affect arm fatigue with relatively low pitch counts, and early OTUTR may lead to early reduction in ball velocity.